2001
DOI: 10.1086/322273
|View full text |Cite
|
Sign up to set email alerts
|

The Electrostatic Screening of Nuclear Reactions in the Sun

Abstract: We apply the method of Shaviv & Shaviv to evaluate from Ðrst principles the plasma screening correction to the rate of nuclear reactions under conditions similar to those prevailing in the present-day Sun. We calculate the screening factor for the p-p chain and the CN cycle nuclear reactions. We Ðnd the following :1. The mean Ðeld approximation la is not strictly valid under the conditions prevaila`Debye-Huckel ing in the core of the Sun. A kinetic approach should be implemented.2. The mean energy exchange bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
1
19
2
Order By: Relevance
“…[91], higher order effects, beyond the Debye-Hückel approximation, modify the screening enhancement in solar fusion reactions by only a very small amount of about 1%. This conclusion is not in accord with results obtained by other authors [92,87].…”
Section: Stellar Electron Screening Problemcontrasting
confidence: 98%
See 2 more Smart Citations
“…[91], higher order effects, beyond the Debye-Hückel approximation, modify the screening enhancement in solar fusion reactions by only a very small amount of about 1%. This conclusion is not in accord with results obtained by other authors [92,87].…”
Section: Stellar Electron Screening Problemcontrasting
confidence: 98%
“…These claims have been substantiated with molecular dynamics calculations [92]. However, it has not been pursued further and has not been verified independently.…”
Section: Stellar Electron Screening Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dappen-Mussak [36,37] and Shaviv [50] have criticized the use of the stationary Salpeter screening. Bahacall et al [51], on the other side, have strongly supported the Salpeter approach in stars, but their arguments have also been criticized [52,53].…”
Section: Validity Of the Ideal Plasma Model: Comments And Requirementsmentioning
confidence: 99%
“…Recently Bahcall et al (2002) (hereafter BBGS) have discussed the Salpeter formula for calculating the electrostatic screening of nuclear reactions in plasma and claim to have shown that it should apply to the Sun and that all claims concerning dynamic effects are wrong, including the recent results of Shaviv & Shaviv (2001) (hereafter SS01). The discussion of BBGS is based on the assumption that the mean field electrostatic potential is a good assumption ignoring the fact that in the core of the Sun this very assumption may not be justified.…”
Section: Introductionmentioning
confidence: 99%